Cultural Resilience of Kejawen Adherents in Surakarta - Verra Yuniar Kusumasari (International Islamic Schools Alliance, 2025)
Kejawen is a view of life system adhered and still maintained since it contains deep cultural values and still related to the ancestor teachings. In this current era, Kejawen needs resilience method to confront the challenges described as ability of individual or community to survive, adapt, and grow. This research used qualitative method and Focus Group Discussion with phenomenological approach. The selection process of the informants was conducted by snowball sampling technique and the initial selection of informants becomes a key to find next informant. Data collection was carried out by interview, observation, and documentation. Validity testing of research data used source triangulation technique by interviewing Kejawen adherent. The research findings showed that the appearance of inhibiting factors becomes challenges for Kejawen adherents in Surakarta to preserve its existence. The challenges were responded by the adherents through several strategies as their resilience form. These strategies included adaptation to current development through innovative use of technology as media in spreading cultural tradition to keep it relevant to young people.